Isolation of Bioactive Compounds from Aspergillus terreus LS07 - Rizna Triana Dewi; Sanro Tachibana; Puspa Dewi; L.B.S. Kardono; Muhammad Ilyas (Universitas Gadjah Mada, 2014)
This study aims to search for the active components from Aspergillus terreus LS07 which isolated from an Indonesian soil. Bioassay-guided fractionations of the ethyl acetate (EtOAc) extract against α-glucosidase and DPPH free radical to give four isolated compounds: oleic acid (1), ergosterol (2), butyrolactone I (3), and butyrolactone II (4). The structures of these metabolites were assigned on the basis of detailed spectroscopic analysis. Oleic acid (1) was showed significant activity toward α-glucosidase with IC50 value of 8.54 μM, but not for antioxidant. Butyrolactone I (3) and II (4) were showed significant activities against the α-glucosidase with their IC50 values at 52.17 and 96.01 μM, and those against DPPH free radicals at 51.39 and 17.64 μM, respectively. On the other hand, ergosterol (2) did not show any activities.